Konflik Sosial Keagamaan Islam Non-Mainstream dalam Masyarakat Majemuk di Indonesia - Zainal Said (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
This paper discusses how Islamic religious movements in relation to social conflict in the lives of people in Indonesia khsususnya Makassar, with menggacu in the case of the non-Islamist movements such as the Ahmadiyah congregation maisntream and An-Nadzir. A group of local religious activity can trigger social conflict which considered deviant religious teachings of the dominant religion. Of social conflict, can lead to violence on the grounds of blasphemy, which is triggered by the presence of the social activities of religious communities or followers of certain religious ideas are somewhat different or perceived menyempal (non-mainstream) of the religion practiced in general (mainstream) in the life of Indonesian society. Conflict is often the case in Indonesia in recent years often contain a complex load. Arguably, political charged presumably still dominant influence, in addition to the problems and feelings suppressed disappointment so far.